X-ray structures from outflowing Young Stellar Objects interacting with the Interstellar Medium - Orellana, Mariana Dominga (2012)
Fil: Orellana, Mariana. Instituto Argentino de Radioastronomía, CONICET-UNLP, La Plata, Argentina.